A rare germline mutation reverses the suppressive effect of GPC5 thereby promoting lung adenocarcinoma development and tumorigenesis - Zheng, Zhifa; Zhao, Lina; Zhao, Sen; Wu, Zhihong; Wu, Nan (Frontiers in Genetics, 2025)
Background and ObjectiveGlypican-5 (GPC5) has been well-characterized as a tumor suppressor in lung adenocarcinoma (LUAD); however, the functional implications of its germline mutations in cancer pathogenesis remain largely unexplored. In this study, we identified and characterized a pathogenic GPC5 variant (c.776C>T, p.Pro259Leu) within a Chinese LUAD pedigree, systematically investigating its oncogenic mechanisms through comprehensive molecular and cellular analyses.MethodsOur investigation employed a multifaceted approach beginning with the recruitment of a LUAD-affected family cohort (n=4 patients, 1 healthy control), followed by exome sequencing of matched blood and FFPE tumor samples. Through rigorous rare variant analysis, we prioritized the GPC5 c.776C>T variant, subsequently validating its pathogenicity via integrated computational modeling and immunohistochemical profiling. Mechanistic studies in A549 and H2009 LUAD cell lines encompassed: (1) comprehensive proliferation and apoptosis assessment using CCK-8, colony formation, EdU incorporation, and flow cytometry; (2) migration and invasion evaluation through Transwell and wound healing assays; (3) EMT/Wnt pathway interrogation via Western blot analysis of E-cadherin, N-cadherin, Vimentin, and β-catenin expression patterns; and (4) definitive functional validation through GPC5 overexpression and knockdown experiments.ResultsGenetic analysis revealed the GPC5 c.776C>T variant exhibited complete cosegregation with LUAD phenotype in the pedigree while being absent in control populations (gnomAD frequency: 0.000003989), accompanied by significantly reduced GPC5 expression in tumor tissues. Functional characterization demonstrated that compared to wild-type, the mutant variant conferred aggressive oncogenic properties: significantly enhanced proliferative capacity, impaired apoptosis induction, and markedly increased migratory potential. Molecular analyses revealed the mutant promoted EMT activation through nuclear β-catenin accumulation and subsequent upregulation of mesenchymal markers. Crucially, siRNA-mediated GPC5 knockdown phenocopied these oncogenic effects, providing definitive evidence of its tumor-suppressive function.DiscussionOur findings establish that the GPC5 c.776C>T mutation drives LUAD progression through a novel molecular mechanism involving impaired β-catenin degradation, subsequent nuclear translocation, and consequent EMT activation. These results position GPC5 as a critical nodal regulator of Wnt/β-catenin signaling in LUAD pathogenesis and suggest its germline mutations may serve as valuable biomarkers for hereditary LUAD risk assessment. Therapeutically, these findings highlight the potential utility of Wnt pathway inhibitors in managing GPC5-mutant LUAD cases, while also providing a molecular framework for future investigations into glypican family members in cancer biology.